Avaliação da disponibilidade de potássio em pó de brita derivado de rochas da Suíte Intrusiva Tracuateua via tratamento termoquímico - SENA, Wesley Achilles Oliveira de (2020)
Brazil has limited reserves of soluble potassium minerals, which cannot meet domestic demand, especially for the production of agricultural fertilizers, which makes the country a major importer of this commodity. On the other hand, a wide occurrence of potassium silicates in the national territory, little explored commercially, has stimulated the search for new technological routes to increase the reactivity of such minerals and to use them as alternative sources to obtain potassium. In this context, heat treatments of potassium silicates in the presence of a fusion agent (FA) have been shown to be an efficient technique for K extraction since it can remobilize it and form new soluble amorphous and/or crystalline phases which are rich in this nutrient. Thus, this study aimed to evaluate the calcination of a K-rich silicate powder gravel (PG) in the presence of different concentrations of an FA, the calcium chloride, for the increase of potassium availability. We defined four mix conditions based in FA/PG ratios (0/1, 0.1/1, 0.2/1 and 0.3/1) for the calcination process at 800 °C for 60 minutes. In order to characterize and investigate the gravel by-product transformations, we performed X-ray fluorescence spectroscopy (XRF) and X-ray diffraction spectroscopy (XRD) analyzes, backscattered electron image acquisition (BSE), and Dispersive Energy Spectrometry (EDS) analysis obtained by Scanning Electron Microscope (SEM). Also, we evaluated the soluble potassium content as a function of different extraction methods (water and 2% citric acid) by Flame Photometry. The calcination of the PG in the absence of FA was not effective to increase potassium availability. On the other hand, calcination with the addition of FA in the (FA/PG) 0.1/1, 0.2/1 and 0.3/1 proportions promoted, respectively, an extraction of 14.9%, 35.5%. and 45.1% of the total amount of K2O present in the PG after extraction in water and 16.2%, 70.0% and 67.3% after extraction in 2% citric acid. The XRD and SEM-EDS analysis of the products of the FA-calcination process indicate that the increase of potassium availability is directly related to the formation of sylvite by K remobilization of the potassium silicate structure. Therefore, the calcination process of potassium silicates in the presence of calcium chloride was efficient in optimizing the availability of K from a raw material of low solubility. For that reason, the final products of thermochemical treatment may represent an alternative source for the production of this commodity.